Extraction of high quality DNA from seized Moroccan cannabis resin (Hashish). - Moulay Abdelaziz El Alaoui (Public Library of Science (PLoS), 2013)
The extraction and purification of nucleic acids is the first step in most molecular biology analysis techniques. The objective of this work is to obtain highly purified nucleic acids derived from Cannabis sativa resin seizure in order to conduct a DNA typing method for the individualization of cannabis resin samples. To obtain highly purified nucleic acids from cannabis resin (Hashish) free from contaminants that cause inhibition of PCR reaction, we have tested two protocols: the CTAB protocol of Wagner and a CTAB protocol described by Somma (2004) adapted for difficult matrix. We obtained high quality genomic DNA from 8 cannabis resin seizures using the adapted protocol. DNA extracted by the Wagner CTAB protocol failed to give polymerase chain reaction (PCR) amplification of tetrahydrocannabinolic acid (THCA) synthase coding gene. However, the extracted DNA by the second protocol permits amplification of THCA synthase coding gene using different sets of primers as assessed by PCR. We describe here for the first time the possibility of DNA extraction from (Hashish) resin derived from Cannabis sativa. This allows the use of DNA molecular tests under special forensic circumstances.